2010
DOI: 10.1038/modpathol.2010.42
|View full text |Cite
|
Sign up to set email alerts
|

HFE mutations in α-1-antitrypsin deficiency: an examination of cirrhotic explants

Abstract: Increased iron deposition is often seen in liver explants with a-1-antitrypsin deficiency, but it remains unclear if this is a nonspecific effect of end-stage liver disease or if individuals with a-1-antitrypsin deficiency and excess iron are at increased risk for HFE mutations. To further examine this question, 45 liver explants with a-1-antitrypsin deficiency and 33 control livers with chronic hepatitis C were examined for histological iron accumulation, graded on a scale of 0 to 4 þ , and HFE mutations. Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 17 publications
(21 reference statements)
0
8
0
1
Order By: Relevance
“…In fact, some previously published work already shown that HFE mutations could modify disease severity in cystic fibrosis [55] as it was already observed for 1ATD [46]. …”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In fact, some previously published work already shown that HFE mutations could modify disease severity in cystic fibrosis [55] as it was already observed for 1ATD [46]. …”
Section: Discussionmentioning
confidence: 87%
“…Hepatocytes are the main site of synthesis of HFE and play a major role in the pathophysiology of Hemochromatosis [45]. HFE have two common alleles, C282Y and H63D [45], and while clinical hemochromatosis is mostly associated with C282Y homozygosity while the frequency of H63D alleles is higher in 1ATD patients versus in the general population (42 vs 27%) [46]. Further analysis showed that HFE variants were significantly associated with higher liver iron deposits in cases of 1ATD, but not hepatitis C-related cirrhosis.…”
Section: Resultsmentioning
confidence: 99%
“…Validation of Scheuer’s classification by comparison with biochemical determination of liver iron content was, until recently, based mainly on a report published in the 1990s by Scheuer’s group in thalassemia major patients treated with the chelator desferrioxamine, but recent publications have also shown its validity in alcoholic liver disease and sickle cell disease [29, 30, 31]. It is also noteworthy that recent publications on the epidemiology of iron-overload diseases in African-American and cirrhotic explants of alpha1-antitrypsin deficiency used Perls’ histological grading as the mainstay of their research [32, 33]. …”
Section: Discussionmentioning
confidence: 99%
“…The high frequency of the HFE mutations in the general population can complicate the interpretation of serum and hepatic iron perturbations in chronic liver diseases that have well-defined etiologies [81,149,[154][155][156]. Screening studies for C282Y disclosed its presence in 12% of patients with chronic hepatitis C and 4% of patients with cryptogenic cirrhosis [156].…”
Section: Cryptogenic Chronic Hepatitis and Hereditary Hemochromatosismentioning
confidence: 99%